The Realm of Last Chances - Yarbrough, Steve, 1956- (New York Vintage Contemporaries, Vintage Books, 2014)
"When Kristin Stevens loses her job at a prestigious California University, she and her husband, Cal, relocate to Massachusetts, where Kristin is forced to take a position at a third-tier college. Kristin becomes entangled in the internal politics of academia, where Cal spends his days alone, fixing up their new home. Soon, Kristin finds herself drawn to their younger neighbor, first as platonic confidants bound by a love of literature and then, inevitably, as something more. In The realm of last chances, Steve Yarbrough gives us a richy nuanced portrait of relationships, loneliness, and a marriage, reinvented."--Page 4 of cover.
Keywords: Married people -- New England -- City and town life